ANALISIS HADIS ETIKA DALAM EKONOMI DAN BISNIS ISLAM - Mohammad Irfani, Mohammad Irfani (Al-Bayan: Journal of Hadith Studies, 2026)
Islamic economic and business ethics is a behavior that reflects a person's morals or in other words actors related to ethics, tend to produce good behavior in every activity or action, without exception in business activities. Concretely, it can be illustrated that if a business person cares about ethics, it can be predicted that he will be honest, trustworthy, fair, always see the interests of other people and so on. By paying attention to the principles and ethics of Islamic business, a person will avoid various business practices that are prohibited by religion, and can make the business he runs have the value of worship before Allah SWT. This study aims to analyze how ethical Hadith in Islamic economics and business. This study uses Documentation data sources, which are data and information collection techniques through searching and finding evidence. Documents are records of past events. Documents can be in the form of writing, or monumental works of a person. The results of the analysis and discussion of ethical Hadith in Islamic economics and business are the First Shiddiq, namely the ethics of the two people who transact so that they are equally honest and do not harm either party. Second, Amanah, namely a trader or businessman who is trustworthy in the sense of not exaggerating the scales and giving bad goods to buyers and is trustworthy in carrying out their duties so that in the last days they will be lucky people. The third is Tabligh, namely a Muslim entrepreneur who is able to communicate his business and promote his business to consumers and the general public in a correct and honest way, so that the business being developed is known by the public and liked so they are happy to buy it. The fourth Fathanah is a business person who understands, understands, and explores all matters relating to all kinds of things that exist in the business world.